Effects of thymol and isoeugenol feed supplementation on quail adult performance, egg characteristics and hatchling success - Luna, Agustin (2012)
1. A study was conducted to evaluate whether feed supplementation with thymol or isoeugenol can alter Japanese quail growth rate and final body weight, the female onset of puberty, henday egg production and the physical and chemical characteristics of the egg, as well as its potential to alter hatchability. 2. From 4 to 16 weeks of age, birds from each cage (1 male: 3 females) were assigned to 1 of 3 treatments that differed in the supplement added to the feed: control, thymol or isoeugenol (400 mg/kg). The average ages (d) at first egg lay (FIRST), at 25% egg production (A25% EP), at 50% egg production (A50% EP) and weekly and cumulative hen-day egg production (HDEP) were calculated. In addition, physical and chemical characteristics of the eggs, their fertility and hatchability were also evaluated for each group. 3. Feed supplementation did not significantly affect growth rate, final body weight, egg production parameters, fertility and physical characteristics of egg or most of the fatty acid components of the yolk. 4. The group treated with isoeugenol showed an increase in the percentage of palmitoleic fatty acidcompared to the control, with thymol group showing intermediates values. 5. Both thymol and isoeugenol supplemented groups showed increased hatchabilities, by 188% and 118%, respectively, compared to their control counterparts. 6. The improvement in the hatching success of the eggs from the thymol and isoeugenol supplemented groups without a negative impact on their performance may have important economic implications for future breeding programmes, particularly if these effects generalise from quail to other more commercially important poultry species, such as chickens or turkeys.